Prevalence of dentigerous cysts due to impaction of mandibular third molar teeth - Nuraini, Hanifah; Yusuf, Harmas Yazid; Hardianto, Andri (Padjadjaran Journal of Dentistry, 2013)
Dentigerous cyst is an odontogenic cyst that surrounds the crown of an impacted tooth, caused by fluid accumulation between the reduced enamel epithelium and the enamel surface, usually associated with mandibular third molars. The purpose of this study was to find out the prevalence of dentigerous cyst caused by impaction of mandibular third molar at the oral and maxillofacial surgery department of Hasan Sadikin hospital Bandung. This study was a descriptive survey study. Samples were taken from the data of patientâs medical record from July 2006 until June 2011. The result of this study showed the number of oromaxillofacial cyst cases in the period was as much as 316 (0.78%). Dentigerous cyst was the most common odontogenic cyst (48,64%). Dentigerous cyst most commonly caused by impaction of the mandibular third molar (13,89%). The amount of male and female patients with dentigerous cyst was the same (50% each). The most age group that suffered dentigerous cyst due to impaction of the mandibular third molars was the age group of 41-50 years (40%). The most chosen therapy was enucleation (100%). From the results of this study can be concluded that dentigerous cyst due to impaction of mandibular third molars was the most common case, with the same frequency found in both male and female, the most age group of impacted was the age group of 41-50 years old, and the most chosen therapy was enucleation.